Study of the Extraction Kinetics of Lithium by Leaching β-Spodumene with Hydrofluoric Acid - Rosales, Gustavo Daniel (2016)
Parameters affecting the kinetics of the dissolution of β-spodumene with hydrofluoric acid have been investigated. The experimental tests were carried out in a closed vessel. The influence of several parameters, such as stirring speed, temperature, and reaction time were studied in order to deduce the kinetics of the dissolution reaction. The other parameters, particle size −45 µm; HF concentration 4% v/v, and the solid–liquid ratio 0.95% w/v were kept constant. The results indicate that the stirring speed does not have an important effect on the dissolution of the mineral above 330 rpm. The extent of the leaching of β-spodumene increases with temperature and reaction time augmentations. Scanning electron microscope (SEM) analyses of some residues in which the conversion was lower than 30% indicated a selective attack on certain zones of the particle. The treatment of the experimental data was carried out using the Modelado software. The model that best represents the dissolution of the mineral is the following: ln(1 − X) = −b1 [ln(1 + b2t) − b2t/(1 + b2t)]. This model is based on “nucleation and growth of nuclei” theory, and describes the style of attack physically observed by SEM on the residues.